Integrating Public Management and Leadership to Explain Local Government Performance - Herman Herman; Shofia Amin; Sigit Indrawijaya; Sry Rosita (Annals of Management and Organization Research, 2026)
Purpose: This study aims to examine how New Public Management (NPM) inf0luences Public Service Performance through two leadership mechanisms, namely Leadership Behaviour as an instrumental mechanism and Servant Leadership as a value-based mechanism, in Indonesian local government organizations. Methodology: This research was conducted in local government organizations in Indonesia using a quantitative explanatory design. Data were collected through a survey of 385 civil servants in South Korea. The study employed a structured questionnaire and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to test both direct and indirect relationships among variables. Results: The results show that New Public Management has a strong positive effect on both Leadership Behaviour and Servant Leadership. However, only Servant Leadership has a significant direct effect on Public Service Performance and acts as a significant mediating variable between NPM and Public Service Performance. Leadership Behaviour does not have a significant direct effect on Public Service Performance. Conclusions: The study concludes that managerial reforms alone are insufficient to improve Public Service Performance. Value-based leadership, particularly Servant Leadership, is a crucial mechanism for translating New Public Management reforms into meaningful service outcomes. Limitations: This study is limited by its cross-sectional design and reliance on self-reported data from a single regional context, which may restrict its generalizability. Contributions: This study contributes to the public management literature by integrating managerial reform and leadership and providing empirical evidence of the role of servant-oriented leadership in public sector performance.